2015
DOI: 10.1038/ng.3459
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-function mutations in TNFAIP3 leading to A20 haploinsufficiency cause an early-onset autoinflammatory disease

Abstract: Systemic autoinflammatory diseases are driven by abnormal activation of innate immunity1. Herein we describe a new syndrome caused by high penetrance heterozygous germline mutations in the NFκB regulatory protein TNFAIP3 (A20) in six unrelated families with early onset systemic inflammation. The syndrome resembles Behçet’s disease (BD), which is typically considered a polygenic disorder with onset in early adulthood2. A20 is a potent inhibitor of the NFκB signaling pathway3. TNFAIP3 mutant truncated proteins a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
476
2
20

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 532 publications
(538 citation statements)
references
References 48 publications
15
476
2
20
Order By: Relevance
“…TNFAIP3 SNPs that in some cases function to reduce A20 expression levels have been identified that confer susceptibility to rheumatoid arthritis, systemic lupus erythematosus, psoriasis, and Behçets disease (37)(38)(39)(40). A recently described familial syndrome with reduced A20 function as a result of haploinsufficiency exhibits inflammatory disease phenotypes that are similar to those with ΔCT-NEMO mutation (41). Therefore, our findings underscore the functional importance of A20 in preventing inflammatory disease in humans.…”
Section: Discussionsupporting
confidence: 50%
“…TNFAIP3 SNPs that in some cases function to reduce A20 expression levels have been identified that confer susceptibility to rheumatoid arthritis, systemic lupus erythematosus, psoriasis, and Behçets disease (37)(38)(39)(40). A recently described familial syndrome with reduced A20 function as a result of haploinsufficiency exhibits inflammatory disease phenotypes that are similar to those with ΔCT-NEMO mutation (41). Therefore, our findings underscore the functional importance of A20 in preventing inflammatory disease in humans.…”
Section: Discussionsupporting
confidence: 50%
“…This is the second report of human germline mutations in a deubiquitinase protein leading to an inflammatory phenotype, the first being mutations in DUB A20 (10). In contrast, deficiency of another deubiquitinase CYLD, which hydrolyzes both Met1 and K63 ubiquitin chains, leads to cylindromatosis (19).…”
Section: Discussionmentioning
confidence: 99%
“…OTULIN is an evolutionarily highly conserved protein, and in mice complete deficiency is embryonically lethal (8). Recently, we reported patients with heterozygous germline mutations in TNFAIP3/ A20 (10), which has DUB activity for K63-linked polyubiquitin chains. Both OTULIN and A20 are important gatekeepers of innate immunity (7,11).…”
mentioning
confidence: 99%
“…Increased inflammation driven by constitutively active NF-κB in patients does not seem to result in a significant increase in IL-1 or IL-18 unless their cells are treated with LPS [116] . NLRP3 expression appears to be increased and therefore primed, as…”
Section: Monogenic Autoinflammatory Diseasementioning
confidence: 99%
“…(HA20, haploinsufficiency of A20) [116] . Increased inflammation driven by constitutively active NF-κB in patients does not seem to result in a significant increase in IL-1 or IL-18 unless their cells are treated with LPS [116] .…”
Section: Monogenic Autoinflammatory Diseasementioning
confidence: 99%